2022
DOI: 10.3390/su14031513
|View full text |Cite
|
Sign up to set email alerts
|

Towards Road Sustainability—Part I: Principles and Holistic Assessment Method for Pavement Maintenance Policies

Abstract: Assessing the holistic sustainability of public policies remains a challenge rarely taken up due to a lack of adequate assessing methods. Frequently, only environmental and/or financial aspects are addressed, rather than the three pillars, including macro- and micro-economic as well as social performance. This paper presents an assessment method to fully compare the performance of pavement resurfacing policies for all its stakeholders and considering pavement–vehicle interactions. First, an analytical and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Roads are key infrastructures that support most of the world's transportation activity [1,2], explaining the wide corpus of research on their sustainability [3]. However, the studies carried out around sustainability solutions are fragmentary, often approached through the prism of a single discipline, as shown in the literature review of part I of this double article on pavement sustainability assessment [4]. Examining these solutions quantitatively through a holistic assessment to quantify the levers of sustainability is needed to develop sound public policy recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roads are key infrastructures that support most of the world's transportation activity [1,2], explaining the wide corpus of research on their sustainability [3]. However, the studies carried out around sustainability solutions are fragmentary, often approached through the prism of a single discipline, as shown in the literature review of part I of this double article on pavement sustainability assessment [4]. Examining these solutions quantitatively through a holistic assessment to quantify the levers of sustainability is needed to develop sound public policy recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Examining these solutions quantitatively through a holistic assessment to quantify the levers of sustainability is needed to develop sound public policy recommendations. This is the challenge that we address in this article on the issue of road maintenance, by applying the holistic method developed in part I of this double article [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pn Pl Ci floor Cl (5) where Pl is the image capture interval, Cl is the road unit length, Pn is the image sequence number, and floor indicates rounding down.…”
Section: Fusion-based Computation Of Defect Data At the Road Unit Levelmentioning
confidence: 99%
“…In recent years, propelled by the rapid evolution of artificial intelligence technology, deep learning techniques have found extensive application in the intelligent identification of road defects [1][2][3][4] , emerging as a significant tool to complement urban road maintenance decision-making [5][6][7][8] . Xiao Liyang et al [9] enhanced the Mask R-CNN model, achieving precise localization and extraction of road surface cracks under high thresholds through a cascade of multiple detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Given that VOP and LOS also show a low level of productivity, it can be concluded that options should be considered to increase the capacity of the road, for example, by adding a lane or building an alternative road (Figure 3). AADT forecast for the period 2023-2032 [12]. Referring to the results from Table 3, the Service Level for 2032 would be 0.79, or referring to Table 1, the Service Level is in Service Level (LOS) D conditions, which stands for "Long Manoeuvring Restrictions".…”
Section: Technical Datamentioning
confidence: 99%